The role of mitochondria in tumor metastasis and advances in mitochondria-targeted cancer therapy - Chen, Fanglu; Xue, Yucheng; Zhang, Wenkan; Zhou, Hao; Zhou, Zhiyi; Chen, Tao; YinWang, Eloy; Li, Hengyuan; Ye, Zhaoming; Gao, Junjie; Wang, Shengdong (Cancer and metastasis reviews, 2024)
Mitochondria are central actors in diverse physiological phenomena ranging from energy metabolism to stress signaling and immune modulation. Accumulating scientific evidence points to the critical involvement of specific mitochondrial-associated events, including mitochondrial quality control, intercellular mitochondrial transfer, and mitochondrial genetics, in potentiating the metastatic cascade of neoplastic cells. Furthermore, numerous recent studies have consistently emphasized the highly significant role mitochondria play in coordinating the regulation of tumor-infiltrating immune cells and immunotherapeutic interventions. This review provides a comprehensive and rigorous scholarly investigation of this subject matter, exploring the intricate mechanisms by which mitochondria contribute to tumor metastasis and examining the progress of mitochondria-targeted cancer therapies.